Early response assessment of glioma patients to definitive chemoradiotherapy using chemical exchange saturation transfer imaging at 7 T. Issue 4 (12th March 2019) - Meissner, Jan‐Eric; Korzowski, Andreas; Regnery, Sebastian; Goerke, Steffen; Breitling, Johannes; Floca, Ralf Omar; Debus, Jürgen; Schlemmer, Heinz‐Peter; Ladd, Mark Edward; Bachert, Peter; Adeberg, Sebastian; Paech, Daniel
Abstract : Background: Patients with newly diagnosed inoperable glioma receive chemoradiotherapy (CRT). Standard Response Assessment in Neuro‐Oncology (RANO) takes a minimum of 4 weeks after the end of treatment. Purpose/Hypothesis: To investigate whether chemical exchange saturation transfer (CEST) MRI enables earlier assessment of response to CRT in glioma patients. Study Type: Longitudinal prospective study. Population: Twelve brain tumor patients who underwent definitive CRT were included in this study. Three longitudinal CEST MRI measurements were performed for each patient at 7T: first before, second immediately after completion of CRT, and a third measurement as a 6‐week follow‐up. Field Strength/Sequence: Conventional MRI (contrast‐enhanced, T2 w and diffusion‐weighted imaging) at 3T and T2 w and CEST MRI at 7T was performed for all patients. Assessment: The mean relaxation‐compensated relayed nuclear‐Overhauser‐effect CEST signal (rNOE) and the mean downfield‐rNOE‐suppressed amide proton transfer (dns‐APT) CEST signal were investigated. Additionally, choline‐to‐N‐acetyl‐aspartate ratios (Cho/NAA) were evaluated using single‐voxel 1 H‐MRS in six of these patients. Performance of obtained contrasts was analyzed in assessing treatment response as classified according to the updated RANO criteria. Statistical Test: Unpaired Student's t ‐test. Results: The rNOE signal significantly separated stable and progressive disease directly after the end of therapy (post‐treatment normalized to pre‐treatment mean ± SD: rNOEresponder = 1.090 ± 0.110, rNOEnon‐responder = 0.808 ± 0.155, P = 0.015). In contrast, no significant difference was observed between either group when assessing the normalized dns‐APT (dns‐APTresponder = 0.953 ± 0.384, dns‐APTnon‐responder = 0.972 ± 0.477, P = 0.95). In the smaller MRS subcohort, normalized Cho/NAA decreased in therapy responders (Cho/NAAresponder = 0.632 ± 0.007, Cho/NAAnon‐responder = 0.946 ± 0.124, P = 0.070). Data Conclusion: rNOE mediated CEST imaging at 7T allowed for discrimination of responders and non‐responders immediately after the end of CRT, additionally supported by 1 H‐MRS data. This is at least 4 weeks earlier than the standard clinical evaluation according to RANO. Therefore, CEST MRI may enable early response assessment in glioma patients. Level of Evidence : 1 Technical Efficacy Stage : 5 J. Magn. Reson. Imaging 2019;50:1268–1277.